Employees’ organizational commitment – risk or preventive factor in professional burnout at work? - Genevičiūtė-Janonienė, Giedrė; Skučaitė, Rūta; Endriulaitienė, Auksė (Psichologija, 2015)
Organizational commitment is an important factor in the prediction of lower absenteeism, greater work motivation, citizenship behavior, and work productivity. Some authors argue that the greater employees’ organizational commitment decreases professional burnout as well. However, recent studies usually employ the emotional component of commitment in such kind of investigations, while continuance and normative commitment are under-investigated. The literature suggests that the development of the components of organizational commitment is related to different reasons and leads to different subsequences of employees’ thinking and behavior. Therefore, the aim of this study was to determine the importance of three components of organizational commitment (emotional, continuance, and normative) for the employees’ burnout (emotional exhaustion, depersonalization, and professional efficacy). It was predicted that a greater emotional commitment would be negatively related to emotional exhaustion and depersonalization and positively related to professional efficacy. The greater continuance commitment would be positively related to emotional exhaustion and depersonalization and negatively related to professional efficacy. The greater normative commitment would be positively related to emotional exhaustion and professional efficacy. In the research, 879 employees from organizations of various size and type participated. There were 402 men and 477 women. They completed the revised version of the Organizational Commitment Questionnaire (Meyer, Allen, & Smith, 1993) which assesses the emotional, normative and continuous commitment, and the Lithuanian version of the Maslach Burnout Inventory MBI-GS (Maslach et al., 1996) which assesses depersonalization, emotional exhaustion and professional efficacy. In order to analyze the interaction among the variables, the linear regression analysis was used. This study highlighted the importance of organizational commitment for employees’ burnout. The results showed that the affective and normative commitment may be an important predictor of a lower emotional exhaustion (β ranged from –0.262 to –0.136) and depersonalization (β ranged from –0.324 to –0.196) of employees. Only emotional commitment can predict greater professional efficacy (β = 0.228). Therefore, the affective and normative commitment should be treated as a preventive factor from burnout, while continuance commitment can predict a stronger employees’ depersonalization (β = 0.142) as well as a higher emotional exhaustion (β = 0.096) and can be attributed to the risk factors in the formation of professional burnout. The findings suggest that organizational commitment can be a useful predictor of employees’ professional burnout, but the different components of organizational commitment should be taken into account.